Provincial variation in colorectal cancer screening adherence in Canada; evidence from the Canadian Partnership for Tomorrow’s Health - Darvishian, Maryam; Moustaqim-Barrette, Amina; Awadalla, Philip; Bhatti, Parveen; Broet, Philippe; McDonald, Kelly; Murphy, Rachel A.; Skead, Kimberly; Urquhart, Robin; Vena, Jennifer; Dummer, Trevor J. B. (Frontiers in Oncology, 2023)
Introduction Although colorectal cancer (CRC) screening program is proven to reduce CRC incidence and mortality, understanding patterns and predictors of suboptimal adherence in screening program requires further investigation in Canada. Methods We used self-reported data from five regional cohorts of the Canadian Partnership for Tomorrow’s Health (CanPath), namely the BC Generations Project (BCGP), Alberta’s Tomorrow Project (ATP), the Ontario Health Study (OHS), Quebec’s CARTaGENE, and the Atlantic Partnership for Tomorrow’s Health Study (Atlantic PATH). We stratified participants into the following four risk categories: 1) age 50-74 years, 2) family history in a first-degree relative, 3) personal history of chronic inflammatory bowel disease and/or polyps, and 4) co-existence of personal risk and family history. Multivariable logistic regression was used to identify predictors of adherence to the screening guidelines. Results Adherence to CRC screening varied considerably between regions, ranging from 16.6% in CARTaGENE to 47.7% in OHS. Compared to the largest cohort OHS, the likelihood of non-adherence to CRC screening was significantly higher in BCGP (OR 1.15, 95% CI 1.11-1.19), the Atlantic PATH (OR 1.90, 95% CI 1.82-1.99) and CARTaGENE (OR 5.10, 95% CI 4.85-5.36). Low physical activity, current smoking, presence of personal risk, family history of CRC significantly reduced the likelihood of adherence to screening recommendations. Discussion/Conclusion Compared to the national target of ≥ 60% for participation in CRC screening, adherence to regular CRC screening was suboptimal in this cohort of Canadians and varied by region. Further efforts are needed to identify the specific barriers to screening adherence in different provinces and across risk categories.